Mitigating Drought Conditions under Climate and Land Use Changes by Applying Hedging Rules for the Multi-Reservoir System - Zejun Li (MDPI AG, 2021)
Climate and land use changes have substantially affected hydrologic cycles and increased the risk of drought. Reservoirs are one of the important means to provide resilience against hydrologic variability and achieve sustainable water management. Therefore, adaptive reservoir operating rules are needed to mitigate their adverse effects. In this study, the Hanjiang River Basin in southeast China was selected as the study area. Future climate and land use projections were produced by the Delta method and CA-Markov model, respectively. Future climate forcings and land use patterns were then incorporated into a distributed hydrologic model to evaluate river flow regime shifts. Results revealed that climate and land use changes may lead to severe drought conditions in the future. Lower flows are shown to be more sensitive to environmental changes and a decline of monthly flows could reach up to nearly 30% in the dry season. To address the threat of increasing drought uncertainties in the water supply system, the aggregation-decomposition method incorporated with hedging rules was applied to guide the multi-reservoir operation. Parameters of optimal hedging rules were obtained by a multi-objective optimization algorithm. The performance of hedging rules was evaluated by comparison to standard operating policies and conventional operating rules with respect to reliability, resiliency, vulnerability, and sustainability indices. Results showed that the multi-reservoir system guided by hedging rules can be more adaptive to the environmental changes.